Answer:
17
Step-by-step explanation:
The top angle is 90 degrees, so I would assume that m<1 is 90 degrees. Plugging this into the equation gives us 90 = 4y + 22. Subtract 22 from both sides, and we get 68 = 4y. Divide both sides by 4, and we get 17 = y.
Whats the question that you need help with?
F(x) = 4 - x² g(x) = 6x
(g - f)(x) = g(x) - f(x)
(g - f)(3) = g(3) - f(3)
g(x) = 6x
g(3) = 6*3 = 18
f(x) = 4 - x²
f(3) = 4 - 3² = 4 - 9 = -5
(g - f)(3) = g(3) - f(3) = 18 - (-5) = 18 + 5 = 23
(g - f)(3) = 23
Answer:
The answer for this question is-4